Beyond famines: wartime state, society, and politicization of food in colonial India, 1939 – 1945 - Sarkar, A (2017)
This thesis explores the origin of one of the most engrossing concerns of the post-colonial Indian state, that is, its extensive, intricate, and expensive feeding arrangements for the civilians. It tracks the colonial origin of the post-colonial welfare state, of which state-management of food is one of the most publicized manifestations. This thesis examines the intervention of the late colonial British state in food procurement and distribution in India during the Second World War, and various forms of such intervention, such as the introduction of food rationing and food austerity laws. It argues that the war necessitated actions on the part of the colonial state to secure food supplies to a vastly expanded British Indian Army, to the foreign Allied troops stationed in India, and to the workers employed in war-industries. The thesis brings forth the constitutional and political predicaments that deprived the colonial central government’s food administration of success. It further reveals how the bitter bargaining about food imports into India between the Government of India and the War Cabinet in Britain hampered the state efforts to tackle the food crisis. By discussing the religious and cultural codes vis-à-vis food consumption that influenced government food policies, this thesis has situated food in the historiography of consumption in colonial India. In addition to adopting a political approach to study food, it has also applied sociological treatment, particularly while dealing with how the wartime scarcity, and consequent austerity laws, forced people to accept novel consumption cultures. It also contributes to the historiography of ‘everyday state’. Through its wartime intervention in everyday food affairs, the colonial state that had been distant and abstract in the perception of most common households, suddenly became a reality to be dealt with in everyday life within the domestic site. Thus, the macro state penetrated micro levels of existence. The colonial state now even developed elaborate food surveillance to gather intelligence about violation of food laws. This thesis unravels the responses of some of the political and religious organizations to state intervention in quotidian food consumption. Following in this vein, through a study of the political use of famine-relief in wartime Bengal, it introduces a new site to the study of communal politics in India, namely, propagation of Hindu communal politics through distribution of food by the Hindu Mahasabha party. Further, it demonstrates how the Muslim League government’s failure to prevent the Great Bengal Famine of 1943-44 was politically used by the Mahasabha to oppose the League’s emerging demand for the creation of Pakistan.